2020
DOI: 10.1177/1078155220934162
|View full text |Cite
|
Sign up to set email alerts
|

Age demographics of subjects enrolled in interventional phase 3 multiple myeloma clinical trials

Abstract: The mean and median ages of diagnosis of multiple myeloma range from 70 to 73 years old, with 63% of patients being over the age of 65. Phase 3 clinical trials are designed to study efficacy in the target disease population and are meant to have the most representative subject pool. The purpose of this review is to identify the age demographic of subjects participating in interventional phase 3 clinical trials that aim to treat multiple myeloma and to determine if they encompass the true age demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Between 2014 and 2017, 39% of the 3612 participants were ≥ 65 years of age [ 11 ]. Borad et al reported younger patients being enrolled more than the true demographic of multiple myeloma in phase 3 clinical trials [ 12 ]. Randomized clinical trials observing drug interventions for ischemic heart disease starting from 2006 and after to measure the exclusion of the elderly population were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2014 and 2017, 39% of the 3612 participants were ≥ 65 years of age [ 11 ]. Borad et al reported younger patients being enrolled more than the true demographic of multiple myeloma in phase 3 clinical trials [ 12 ]. Randomized clinical trials observing drug interventions for ischemic heart disease starting from 2006 and after to measure the exclusion of the elderly population were examined.…”
Section: Introductionmentioning
confidence: 99%